Take a Mixed Approach to Mixing. Issue 5 (2nd May 2019) - Malinaro, Ann; Rhoades, Jacqueline; Pennock, William; Gutierrez, Felipe
Abstract : Authors' note: This column, prepared by members of the AWWA Coagulation and Filtration Committee, is the first in the series "Hot Topics in Water Quality, " presented by the Water Quality Technology Division, as introduced in the April 2019 issue of Journal AWWA . Next month's column will feature hot topics from the AWWA Source Water Protection Committee .